Nerve growth factor induces the association of a 130-Kd phosphoprotein with its receptor in PC-12 pheochromocytoma cells. - Ohmichi, M (1991)
To explore the molecular mechanisms of nerve growth factor (NGF) action, we have attempted to identify proteins that immunoprecipitate with the NGF receptor. An anti-NGF receptor antibody was developed that immunoprecipitated the 75-Kd receptor in PC-12 cells. In [35S]methionine-labeled cells lysed with nonionic detergent, immunoprecipitation with this antireceptor antisera specifically brought down several associated proteins, although prior treatment of cells with NGF produced no apparent change in the distribution of these proteins. However, in vitro phosphorylation assays of the immunoprecipitated complex revealed the presence of a serine kinase that phosphorylated two predominant substrates with Mrs of 60 and 130 Kd. Prior treatment of cells produced no change in the appearance of the 60-Kd phosphoprotein, but NGF did stimulate the appearance of the 130-Kd protein. This effect was observed with as little as 0.1 nM NGF and was maximal at 5 min, but declined thereafter. Prior treatment of cells with NGF did not increase the phosphorylation of enolase added exogenously to the immunoprecipitates, suggesting that this action of NGF may have reflected the hormone-dependent association of the 130-Kd protein with the receptor, rather than activation of a receptor-associated kinase. Thus the association of the NGF 75-Kd receptor with a 130-Kd protein may be involved in signal transduction for the growth factor, although the role of this receptor in the NGF-dependent tyrosine phosphorylation remains unclear.